FOUNDER OF STEPPE AFFORESTATION AND FOREST MELIORATION (In honor of Georgiy Vysotsky’s 150th birthday) - Tkach, V. P.; Migunova, Ye. S. (Forestry and Forest Melioration, 2018)
The paper characterizes a fundamental contribution of G. N. Vysotsky, who was the scientist of encyclopaedic knowledge, to the development of problems of steppe afforestation nominating him to the position of the founder of steppe forest science and silviculture.